1991
DOI: 10.1071/ea9910551
|View full text |Cite
|
Sign up to set email alerts
|

Cultural practices in the control of bean root rot

Abstract: Bean root rot (a complex of Apharwmyces spp., Fusarium solani f. sp. phaseoli, Pythium spp. and Rhizoctonia solani) affects winter-grown fresh beans at Gympie, Queensland. In 5 trials conducted in 1986-88, cultural practices (depth of planting, depth of cultivation, hilling) and a fungicide treatment were examined as methods of control of the disease. The experiments were sited on a clay-loam soil, and under these conditions, shallow planting (25 mm) was the most effective treatment, significantly (P<0.05) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(16 citation statements)
references
References 4 publications
0
15
0
1
Order By: Relevance
“…Siddique and Loss (1999) reported that the yield of chickpea and faba bean was increased by deep seeding. Another field study showed that shallow seeding (at 2.5 cm depth) was the most effective method among the cultural practices tested (seeding and hilling depth, and fungicide use) to decrease the severity of bean root rot (Brien et al 1991); however, the impacts of those practices on the disease incidence and yield were not determined. To our knowledge, there is no previous report on how strongly planting depth interacts with the components of bean yield and FRR on a regional scale.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Siddique and Loss (1999) reported that the yield of chickpea and faba bean was increased by deep seeding. Another field study showed that shallow seeding (at 2.5 cm depth) was the most effective method among the cultural practices tested (seeding and hilling depth, and fungicide use) to decrease the severity of bean root rot (Brien et al 1991); however, the impacts of those practices on the disease incidence and yield were not determined. To our knowledge, there is no previous report on how strongly planting depth interacts with the components of bean yield and FRR on a regional scale.…”
Section: Discussionmentioning
confidence: 96%
“…Because of noticeable losses to FRR on susceptible beans under environmental stresses (Harveson et al 2005), most previous studies have focused on identifying cultural practices that reduce various types of stress on bean crops. Although irrigation regime, nitrogen fertilization, plant and weed density, planting date and depth, and previous cropping history are known to be important factors affecting FRR development and bean production (Abawi and Widmer 2000;Brien et al 1991;Burke and Miller 1983;Deibert 1995;Kraft et al 1981), regional assessment of the various agronomic factors linked to FRR at different growth stages is not well documented. Although there have been a number of large-scale investigations describing the associations between agricultural and disease variables (Fernandez et al 2007;Fininsa and Yuen 2001;Rodríguez et al 2008;Sahile et al 2008;Workneh et al 1999;Zewde et al 2007), only a few large-scale studies have explored agronomic indicators of yield reductions in pathosystems (Mila et al 2003).…”
Section: Introductionmentioning
confidence: 98%
“…Roots were excised from the plants and data collected for analysis. Data included root and crown rot severity assessed on a rating scale of 0-4 (Brien et al, 1991). where, A is the disease severity exhibited in the root/crown region due to F. oxysporum alone and B is the disease severity exhibited in the root/crown region after inoculation with both the pathogen and bacterial antagonists.…”
Section: Disease Assessmentmentioning
confidence: 99%
“…Few options are available for the control of root rot diseases caused by Fusarium spp. and other fungi in beans (O'Brien et al, 1991). Seed treatments with chemical fungicides provide only a small zone of protection around the seed, which limit their efficacy (Conner et al, 2014).…”
Section: Introductionmentioning
confidence: 99%